Christian-Muslim relations online - Thomas, David (BrillOnline reference works, 2011)
"Christian-Muslim Relations, a Bibliographical History Online is a general online history of relations between the faiths. It covers the period from 600 to 1500, when encounters took place through the extended Mediterranean basin and are recorded in Syriac, Arabic, Greek, Latin and other languages. Christian Muslim Relations Online comprises introductory essays on the treatment of Christians in the Qur'an, Qur'an commentaries, biographies of the Prophet, Hadith and Sunni law, and of Muslims in canon law, and the main body of more than two hundred detailed entries on all the works recorded, whether surviving or lost."--Publisher information